2010
DOI: 10.2147/vhrm.s9400
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and aspirin use in Asian and Western populations

Abstract: ObjectiveThe aim of this review was to examine aspirin utilization, cardiovascular risk estimation, and clinical evidence for aspirin prophylaxis in Asian versus Western countries.MethodsA literature search was performed using PubMed and the key terms “aspirin” and “Asia” or “Western”.ResultsDespite the growing burden of cardiovascular disease (CVD), aspirin is underutilized in high-risk patients in both Asian and Western countries. A number of risk estimation scores are available; however, validation is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Most patients were naïve to any treatment before study enrollment (Table 1 ), and analgesic use in China is low overall compared with the United States [ 36 ]. It is therefore possible that patients benefitted from initiation of treatment or from encouragement to use analgesics for pain control.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients were naïve to any treatment before study enrollment (Table 1 ), and analgesic use in China is low overall compared with the United States [ 36 ]. It is therefore possible that patients benefitted from initiation of treatment or from encouragement to use analgesics for pain control.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why, for the purposes of this study, we identified a group of people with a SCORE result between 5% and 9%, and considered that they had relative indications for primary cardiovascular preventive therapy. We believe that a SCORE result of 10% or higher better indicates the necessity for cardiovascular pharmacological prevention in older people [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Findings from the landmark Japanese Primary prevention of atherosclerosis with Aspirin for Diabetes (JPAD) trial also support the tolerability and safety of low-dose ASA (80 to 100 mg/day) [37]. As hemorrhagic stroke is more common in the Japanese than Western populations [38], it was encouraging that the risk of hemorrhagic stroke was similar between the treatment and control group in the JPAD trial [37]. Moreover, a 10-year follow-up of the patients enrolled in the original JPAD trial found no increased risk of cardiovascular events with low-dose ASA use but slight increased risk ( p = 0.03) for gastrointestinal bleeding [39].…”
Section: Discussionmentioning
confidence: 95%
“…In the above studies reviewed, there were no reports of any severe adverse events related to ASA use. Findings from the landmark Japanese Primary prevention of atherosclerosis with Aspirin for Diabetes (JPAD) trial also support the tolerability and safety of low-dose ASA (80 to 100 mg/day) [37]. As hemorrhagic stroke is more common in the Japanese than Western populations [38], it was encouraging that the risk of hemorrhagic stroke was similar between the treatment and control group in the JPAD trial [37].…”
Section: Discussionmentioning
confidence: 99%